2013
DOI: 10.1002/jobm.201300457
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of silver nanoparticles with Escherichia coli and their cell envelope biomolecules

Abstract: The antibacterial effect of AgNPs was investigated by determining MIC/MBC and growth kinetics assay. The lowest MIC/MBC was found to be in the range of 11.25-22.5 µg ml(-1) . The growth kinetics curve shows that 25 µg ml(-1) AgNPs strongly inhibits the bacterial growth. Confocal laser scanning electron microscopy (CLSM) shows that as the concentration of NPs increases, reduction in the number of cells was observed and at 50 µg ml(-1) of NPs, 100% death was noticed. Scanning electron microscopy (SEM) shows cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(88 citation statements)
references
References 34 publications
5
83
0
Order By: Relevance
“…[28][29][30] On the other hand, upsurge in resistance to Ag NPs has been reported due to genetic alterations in bacteria. 31 The deposition of silver 32 The high toxicity of CuO NPs causes oxidative lesions, while DNA damage induced by ZnO and TiO 2 NPs limits the efficacy of these NPs. Nonetheless, NPs have emerged as alternative antimicrobial approach to combat biofilms and for treating severe bacterial infections.…”
Section: Nanotechnology-based Therapeutic Interventions To Fight Nosomentioning
confidence: 99%
See 1 more Smart Citation
“…[28][29][30] On the other hand, upsurge in resistance to Ag NPs has been reported due to genetic alterations in bacteria. 31 The deposition of silver 32 The high toxicity of CuO NPs causes oxidative lesions, while DNA damage induced by ZnO and TiO 2 NPs limits the efficacy of these NPs. Nonetheless, NPs have emerged as alternative antimicrobial approach to combat biofilms and for treating severe bacterial infections.…”
Section: Nanotechnology-based Therapeutic Interventions To Fight Nosomentioning
confidence: 99%
“…38 Al 2 O 3 NPs cause oxidative damage to membrane and enter cytoplasm. 32 Ag and Au NPs have been reported to exert toxicity by penetrating inside the cell and denaturing 30S ribosomal subunit, thereby impeding protein translation.…”
Section: Penetration Of the Cell Envelope And Ribosome Destabilizationmentioning
confidence: 99%
“…One of the mechanisms of silver ion release from polymeric matrix occurs through contact of metallic silver with dissolved oxygen in moisture 15,16 . Once released, AgNano will act on the microbial cells through several modes of action 17 , such as: (a) nanoparticles can bind to proteins of vital enzymes presents in the mycelial 18 and bacterial 19 cell wall, (b) also can damage the cellular structures and biomolecules 20 , (c) cause toxicity by the generation of reactive oxygen species 21 , besides (d) affecting in the molecular and cellular routes of bacteria. Recently, silver nanoparticles have been pointed out as the most innovative and efficient antibacterial form 16 , since they provide better dispersion in the polymeric matrix 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Structural changes in the phospholipid lead to the loss of parent molecules, destruction of the cell membrane, and cytoplasmic leakage. 119 One of the foremost functions of the cell membrane is in the respiratory activity of bacteria. Studies have reported that NPs disrupt the respiratory activity of the bacterial cell membrane, which can be analyzed by detecting the uptake of O 2 or the reduction in 2,3,5-triphenyltetrazolium chloride (TTC).…”
mentioning
confidence: 99%